Tuning the nitric oxide release from CPO-27 MOFs. Issue 17 (3rd February 2016) - Cattaneo, Damiano; Warrender, Stewart J.; Duncan, Morven J.; Kelsall, Christopher J.; Doherty, Mary K.; Whitfield, Phillip D.; Megson, Ian L.; Morris, Russell E.
Abstract : Nitric oxide release from CPO-27 MOFs and the resulting coronary artery relaxation response are tuned by isomorphous substitution of Ni into the MOF framework. Abstract : Nitric oxide (NO) storage and release measurements have been recorded for Ni-doped CPO-27 (Mg) and CPO-27 (Zn), and the biological effect of the released NO was assessed in porcine coronary artery relaxation tests. The results indicate that the doping strategy leads to increased levels of NO storage and delivery compared to the parent materials and that the NO dosage and biological response can be tuned via this approach to suit the requirements of particular applications.